Inhibition effect of enhanced oil recovery (eor) surfactant on carbon steel corrosion - Zakaria, W.W.N.L. (Asian Research Publishing Network, 2016)
Injection of surfactants during oilfield production is one of many selections of EOR methods. Besides its main role, the utilization of this chemical enhanced oil recovery (CEOR) has also potential in corrosion mitigation of downhole tube due to its inhibitor properties. In this paper, corrosion mitigation performance of a commercial EOR surfactant with various concentrations under CO2 environment was analyzed using Linear Polarization Resistance (LPR) technique. The functional group of the surfactant was investigated using Fourier Transform Infra-Red (FTIR) while Energy Dispersive X-ray Spectroscopy (EDX) connected to Scanning Electron Microscopy (SEM) was used to study the surface characteristics changes. It was found that the injection of EOR surfactant gives a significant corrosion inhibition effect that varies upon concentration dosage. In this test, the surfactant managed to reduce the corrosion rate of API X65 steel in CO2 environment between 74 - 97 upon injection of 50ppm to 5000ppm surfactant. Higher surface coverage with possible multi-layers protective formation on sample was observed at higher concentration of EOR surfactant injection Â©2006-2016 Asian Research Publishing Network (ARPN).